Sikap Siswa terhadap Video Pembelajaran Jarak Jauh Materi Statistika pada Media Sosial Youtube - Enika Wulandari; Wachid Nugroho (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
This research aims to describe the attitude of grade XII students of SMK Negeri 2 Salatiga towards videos that are functioned as a means of distance learning statistical material uploaded on social media youtube. This research is qualitative research. Data is collected through: 1) the filling out of questionnaires about students' attitudes towards content, contextual nature, interactive nature, accessibility, and video benefits; and 2) interviews to complete the poll data. Poll data is descriptively analyzed to obtain student attitude categories and confirmed with interview data. The results of this study include: 1) students' attitude towards the use of statistical learning videos uploaded on social media youtube is in the category quite well; 2) students' attitudes towards video content are in a good category; 3) the student's attitude towards the contextual nature of the video is in the category quite well; 4) students' attitude towards the interactive nature of the video is in the category quite well; 5) students' attitude to video accessibility is in the category quite well;Â 6) students' attitude to the benefits of video is in the category quite well; 7) Students' attitude towards the look of the video is in the category quite well.